Estudo sobre o polimorfismo dos genes álcool desidrogenase e aldeído desidrogenase (gene adh e aldh) e a dependência ao álcool em uma população da cidade de Goiânia-GO, Brasil - Teixeira, Thallita Monteiro (2016)
Alcoholism is a disease defined as a physical and / or mental condition, which characterized the need of the individual to ingest the substance constantly in order to experience its psychic effects or stop the withdrawal symptoms of the same. Heavy alcohol consumption brings many consequences for the health and quality of life by increasing the frequency of morbidity and mortality, causing several functional limitations. Worldwide, enormous resources are being invested in campaigns against alcohol abuse. WHO, for example, establishing a standard dose contains about 10 to 12 g of pure alcohol equivalent to a can of beer (350 mL) and draft (330 mL), a glass of wine (100ml), or distillate dose (30 mL). Some individuals metabolise alcohol better than others. The main ethanol elimination pathway occurs through oxidation of acetaldehyde to the same and then acid and water. These reactions are catalyzed by the enzyme alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH). In this context, the scientific endeavor of this study to characterize the presence of polymorphisms of ADH and ALDH genes in alcohol users region of the state of Goiás, it is necessary to establish a possible correlation with alcoholism. This study was conducted in Goiás Alcoholics Recovery Center (GO CEREA) and Psychosocial Care Center Alcohol and Drugs (CAPS AD) both in Goiania. For the experiments, a sample of blood from each patient for DNA extraction was collected. Assays were performed by RT-PCR TaqMan SNP Genotyping Assays system. Statistical analyzes were made through GENEPOP 4.5 and Haploview software. Significant differences were found for SNPs studied in the analysis “Case vs. Control” and “Female vs. Male”. Furthermore, binding was observed moderate linkage disequilibrium between the ADH1B*2 and ADH1C*2 SNPs and the presence of haplotype by segregation dependent thereof. These results therefore suggest that these genetic variants may be associated with protection or addiction to alcoholism in the population studied in the city of Goiania, GO, Brazil.